Membangun Generasi Muda yang Demokratis dan Kritis dengan Adanya Demokrasi Subtantif - Rahman, Naziva Azzahra; Sirait, Naomi Margaretha Ghokmaria; Rahmadana, Radya Alluna; Kayla, Syafa Ananda; Fiddien, Muhammad Alizza; Krismianto, Muhammad Ghiza Gema Lani; Nasution, Fakhri Hanif; Suryo, Angger Bagas; Andi Fitra, Taufiqur Rahman; Tarina, Desi Yayi; S, Satino; S, Suprima (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article discusses the development of democratic and critical generations with the presence of substantive democracy in SMAN 1 Parung. The purpose of this study is to illustrate and explain the importance of substantive democracy in society, as well as its application in the government system and the learning process at SMAN 1 Parung. This type of research is quantitative. Observation, interview, and research as key of instruments are some of the tools used in research. This study's data is the result of a seminar for students, as well as discussions with school administrators, curriculum coordinators, and language teachers. Nevertheless, the outcome is an explanation of the significance of substantive democracy and its application in educational settings. The process involves using a method that incorporates substantive democracy into Pancasila education, namely in the areas of pancasila, nationalism, and religion. Improving the character of educationThis education has the potential to increase the quality of learning by making it more pleasant, providing understanding of substantive democracy and its application in the school environment, and being motivating, inspirational, and meaningful. Aside from that, students are inspired to apply character traits in their daily lives such as justice kindness, civility, and honesty